The establishment of a cross-regional differentiated ecological compensation scheme based on the benefit areas and benefit levels of sand-stabilization ecosystem service. (10th October 2020) - Su, Kai; Sun, Xiaoting; Guo, Hongqiong; Long, Qianqian; Li, Song; Mao, Xueqing; Niu, Teng; Yu, Qiang; Wang, Yinran; Yue, Depeng
Abstract: A scientific and reasonable ecological compensation scheme (ECS) is an important guarantee for promoting coordinated and equitable development between regions. The existing ECSs usually ignore the premise that the ECS can only be accepted by the stakeholders if there are a clear scope and benefit to the ecosystem services (ES). An ecological compensation scheme should be based on the transmission principle of ES so that a scientific and reasonable scheme can be proposed and accepted by the stakeholders. Based on the theory of ecosystem service flow, this paper analyzed the provision‒benefit mechanism of sand-stabilization ecosystem service (SSS) and selected Ordos City, Inner Mongolia, which is located in Northwest China, as the study area. A revised wind erosion equation (RWEQ) model was used to estimate the sand-stabilization amount of Ordos's ecosystem in 2015, and a hybrid single-particle Lagrangian integrated trajectory (HYSPLIT) model was used to simulate the path of sand-stabilization ecosystem service flow (SSSF). Then, the benefit areas and levels of SSS were identified, and the spatial distribution of land cover, population, and gross domestic product (GDP) in the ecosystem services beneficiary area (SBA) was evaluated. Based on the identified benefit areas and benefit levels, and combined with the investment and income in the ecological construction of the Ordos, a cross‒regional differentiated ECS was proposed. The results show that the Ordos's ecosystem played a huge role in sand-stabilization, which have brought huge ecological and economic benefits. In 2015, the sand-stabilization amount of Ordos's ecosystem was about 7.20 × 10 8 tons. The area of SBA is 1.66 × 10 6 K m 2, accounting for 17.21% of China's total area, this mainly involves 16 provinces and cities, including Beijing, Tianjin, Hebei, etc . The amount of dust‒fall (ADF) in the beneficiary area was reduced by 28, 738.67 × 10 4 tons, and investment of 4318.51 × 10 8 RMB (Renminbi) in dust removal would be avoided. For the ECS, based on the principle of "equity, beneficiary compensation, more benefit and more compensation", Ordos shall take care of the ecological compensation fee (ECF) of about 36.28% of the total. In 16 provinces and cities, Inner Mongolia costs 66, 121.03 × 10 4 RMB, which is the most. The fees are payable by other SBAs decrease with distance. Hubei Province (Suizhou) pays the least in ecological compensation, at 7.5 × 10 4 RMB. Based on the theory of ecosystem service flow, this paper proposes a research framework of differentiated ECS of SSS, which can provide an accurate scientific basis for determining the SBA and cross-regional ECS of SSS in the future. Graphical abstract: Image 1 Highlights: The benefit mechanism of SSS in SBA are revealed. The scope and benefit levels of SSS in SBA are identified. The ecological and economic benefits of SSS in SBA are estimated. This paper proposes a research framework of cross-regional differentiated ECS of SSS. We estimate the ECFs that should be paid for Ordos in 16 SBA areas in 2015.